The Intentional and Discovering Role of Bin Arabi’s Idea of the Perfect Man in Shiite Imamate as Reflected in Feyz Kashani’s Works - Shahnaz Shayanfar (حکمت اسرا, 2013)
In Bin Arabi’s mystical tradition, after the unity of existence, a central component called “the perfect man” is put forth. Some reviewers have considered the “perfect man” and “monotheism” as the two fundamental issues in theoretical mysticism. Guardianship and the position of Allah’s caliphate, making alterations in the world and being its soul, being the treasurer of the Divine secrets and king appointed by Allah and possessing the ultimate wisdom are but a few of the characteristics of the perfect man. Therefore, the component of the perfect man, just like Sohravardi’s concept of the “Guardian of the Book”, enjoys the characteristics of the Imam in the Shiite traditions the Shiite audience finds it very similar to the example of the “Imam”. The idea of the perfect man within the intellectual framework of Feyz Kashani, as a Shiite intellectual, has led him to pay a novel and more serious attention to those traditions that have been given less attention by the other Shiite intellectuals, especially the theologians; he has been able to discover some hidden implications or prove the obvious implications in the Quranic verses and the traditions by the use of the aforementioned idea. In this paper, the intentional role of the perfect man in Imamate has been studied and, based on Feyz Kashani’s works as well as the idea of the perfect man, the manner of discovering the hidden implications in the traditions with regard to the position of the Imam in the existence and proving the obvious implications has been discussed.